Aspects de la recherche mondiale sur le tournesol - Jouffret Pierre; Labalette Françoise; Lecomte Vincent; Penaud Annette; Pouzet André; Quéré Lionel (Oléagineux, Corps gras, Lipides, 2004)
The 16th International Sunflower Conference was held from August 29th to September 2th, 2004 in Fargo, North Dakota, USA. 250 participants were present and 25 countries were represented. The leaders of the world’s main research programs on sunflower were in Fargo. Consequently, it is possible to sum up the principal orientations of world research on sunflower at present. Concerning disease resistance and pathology, downy mildew and sclerotinia are the main studied topics. Only few studies are carried out on other diseases. The main subject treated in weed control is the selection and efficiency of sunflower varieties with resistance to imidazoline herbicides, to control broomrape and other weeds. For crop production and physiology, the main programs are leaded by Argentina (interesting study about productivity and high densities) and France (Heliotest: a decision support system for nitrogen fertilization). Concerning breeding and genetics, a lot of studies were presented and confirmed a great improvement in the characterization of the genome of sunflower and other compositae. The helianthus wild species germplasm collection which is held in Ames (Iowa) was presented and described. Concerning oil composition, tocopherols and high oleic appeared as the main topics.